2014
DOI: 10.1007/s13187-014-0653-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception, and Attitudes About Cancer and its Treatment Among Healthy Relatives of Cancer Patients: Single Institution Hospital-Based Study in Saudi Arabia

Abstract: This study was conducted to assess knowledge, perception, and attitudes regarding cancer and treatment among healthy relatives of cancer patients who attended an outpatient cancer clinic with their relatives who suffer from cancers. The participants recruited in this cross-sectional, interview-based study were 846 (557 female and 289 male subjects) healthy relatives of cancer patients from the outpatient cancer clinic at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Most of the participants answere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…Typically, cancer is associated with death, fear and emotions such as anxiety, agitation, painful and uncontrollable situation (16). Investigating of women's beliefs about cancer showed that the concepts of fear, mystery, contagion, and stigma are considered as a nature of cancer and lifestyle, stress, environment, genes, unknown causes and destiny are identified as explanations about the cancer causes and in some cases, factors such as black magic were considered as a cause of cancer (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cancer is associated with death, fear and emotions such as anxiety, agitation, painful and uncontrollable situation (16). Investigating of women's beliefs about cancer showed that the concepts of fear, mystery, contagion, and stigma are considered as a nature of cancer and lifestyle, stress, environment, genes, unknown causes and destiny are identified as explanations about the cancer causes and in some cases, factors such as black magic were considered as a cause of cancer (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Nur sehr vereinzelt zeigen Befunde zur Stigmatisierung von Krebspatienten auch Zusammenhänge zu soziodemografischen Merkmalen der Befragten, wobei die wenigen Untersuchungen dazu aus anderen Kulturkreisen stammen und nur bedingt übertragbar sind. Männer und Personen mit geringerem Einkommen, niedrigerer Bildung sowie mit schlechterem Gesundheitszustand bringen eine stärkere Stigmatisierung gegenüber Krebspatienten zum Ausdruck [12,13]. Dabei ist zu beachten, dass Erhebungen zu stigmabezogenen Einstellungen mit sozial erwünschten Antworten korrespondieren können und sozial erwünschtes Antwortverhalten negative Einstellungen nicht oder abgeschwächt reflektiert [14].…”
Section: Einleitung ▼unclassified
“…In anderen Studien wird demgegenüber ein enger Zusammenhang zwischen internal attribuierten Krebserkrankungen (insbesondere Lungenkrebs) und stigmatisierenden Einstellungen gezeigt [9]. Die Ergebnisse zum Zusammenhang von soziodemografischen und persönlichen Merkmalen und der Zustimmung zu stigmatisierenden Aussagen sind konform mit den Befunden aus der Literatur: höhere Zustimmung zu krebsstigmatisierenden Aussagen geben Ältere (> 60 Jahre) sowie Männer [5,12]…”
Section: Zustimmung Zu Stigmatisierenden Aussagen Gegenüber Krebspatiunclassified
“…Despite advances in early detection and treatment, a cancer diagnosis is often considered a death sentence, and negative images and myths regarding cancer persist . Cancer patients frequently do not disclose their diagnosis to avoid discrimination or problems at home, in the workplace, or in society in general . Furthermore, general population surveys show that a substantial proportion of people feel uncomfortable in the presence of cancer patients and tend to avoid interacting or working with them .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, general population surveys show that a substantial proportion of people feel uncomfortable in the presence of cancer patients and tend to avoid interacting or working with them . Discriminatory behavior toward cancer may alienate patients from their community , complicate returning to work after treatment , and have adverse physical and mental health consequences for cancer survivors .…”
Section: Introductionmentioning
confidence: 99%